High temperature π - Amin, M.H.S (IEEE Transactions on applied superconductivity)
A new DC-SQUID is proposed that exploits the properties of the grain boundary junctions in high Tc superconductors. The orientations of the grain boundaries are chosen in such a way to establish a π/2 (rather than 0 or π) phase difference between the equilibrium phases of the two Josephson junctions in the SQUID loop. This property is exploited to increase the sensitivity and direction dependence of the SQUID for measuring magnetic flux without additional flux generating coils.